UV-C seed priming improves tomato plant growth against salt stress. Issue 1 (31st December 2022) - Alamer, Khalid H.; Attia, Houneida
Abstract : The study aimed to evaluate the impact of UV-C dry seed priming at two doses (0.85 and 3.42 kJ.m −2 ), on tomato under salt stress (NaCl, 100 mM). Results show that salinity causes a regression of tomato growth by 63%, an accumulation of Na + causing a reduction in K + uptake and therefore an increase of photosynthetic processes (28, 28 and 23% for Chl. a, Chl. tot and Car., respectively), also an augmentation in soluble protein contents and a decrease or an increase in oxidative stress indicators and secondary metabolites depending on organs. UV-C seed priming has been shown to improve tomato growth by reducing the adverse effects of salinity on physiological and biochemical parameters. This research revealed that UV-C seed applications are an efficient approach to controlling the aggressiveness of salt stress on tomato roots and leaves. Specific doses of UV-C are required to trigger the physiological control of plants against salt stress.